Assessing vaccine hesitancy and health literacy using a new Italian vaccine confidence index and a modified Italian medical term recognition test: A cross-sectional survey on Italian parents - Guglielmo Arzilli; Lorenzo Stacchini; Virginia Casigliani; Sara Mazzilli; Francesco Aquino; Aurea Oradini-Alacreu; Beatrice Bruni; Filippo Quattrone; Francesca Papini; Daniele Sironi; Andrea Davide Porretta; Gaetano Pierpaolo Privitera; et al. (Taylor & Francis Group, 2023)
ABSTRACTThe decline in children's vaccination coverage and the resurgence of preventable infectious diseases draw attention to parents' vaccine hesitancy. Our study introduces two validated tools to independently assess vaccine hesitancy and health literacy among parents with school-age children. We developed a Vaccine Confidence Index (VCI) from 10 Likert items, exploring their relationships through exploratory and confirmatory factor analyses. We modified the IMETER (Italian medical term recognition test) to measure health literacy. We assessed the internal consistency of the modified IMETER and the 10 Likert items using Cronbach's alpha test (α) and McDonald's omega total coefficient (ω) with good results (ω = 0.92, α = 0.90; ω = 0.87, α = 0.82 respectively). We used these tools within a questionnaire conducted on 743 parents recruited from pediatric clinic waiting rooms in Italy, collecting demographic data, information sources on vaccines and vaccine-preventable diseases knowledge. The VCI resulting from factor analyses consisted of six items on a ten-point Likert scale, reflecting the ratio of positive to negative items. The survey revealed significant variations in the VCI according to individual features such as education, use of social networks, or Health institutions as sources of information. Multivariate logistic regression identified an association between vaccine intention and the VCI. Health literacy was functional for 91.2% of participants, but knowledge about vaccine-preventable diseases was generally low. The VCI showed no significant association with health literacy and vaccine-preventable diseases knowledge. The VCI and the modified IMETER effectively assess vaccination attitude and health literacy, offering valuable public health tools for tailoring vaccination campaigns to hesitant population subgroups.